Methods of Developing the Levels of Physical Training of Freestyle Wrestling Girls (Eurasian Scientific Herald, 2022)
Our national struggle is developing widely in many countries of the world. At present, the development of new training methods in order for Uzbek wrestlers to raise the flag of our country at the world arenas is one of the important issues. Therefore, we have used special method of development of physical qualities of wrestlers and presented results in this article.